Case Report: Simultaneous Paragonimus skrjabini infection in twin girls with spontaneous emergence of a juvenile worm from the eyelid of the elder sister - Liu, Jintao; Huang, Liyun (Frontiers in Pediatrics, 2025)
We reported a rare case of paragonimiasis occurring in twin sisters who had eaten raw crabs 7 months ago. The elder sister complained of eyelid swelling and migratory lumps, while the younger sister was asymptomatic. Laboratory tests showed eosinophilia and elevated levels of inflammatory indicators in the two sisters. The brain MRI of the elder twin showed hyperintensity in the frontal lobe, suggesting cerebral hemorrhage. The chest CT image of the twins showed pulmonary involvement. Enzyme-linked immunosorbent assay (ELISA) for serum antibody test and metagenomic next-generation sequencing (mNGS) of subcutaneous tissue from the eyelid—obtained via sterile puncture aspiration under local anesthesia—confirmed Paragonimus skrjabini infection. After praziquantel treatment, both of the sisters recovered. This study aims to enhance clinical awareness and highlight the application of advanced molecular diagnostic technologies for identifying rare parasitic infections.